PENINGKATAN PEMAHAMAN GEOMETRI DAN PENGUKURAN PADA TEMA BUDI PEKERTI MELALUI METODE DEMONSTRASI KELAS III SDN SUMBEREJO II KECAMATAN PAKAL KOTA SURABAYA - Sutriani Sutriani (LPPM STAI Muhammadiyah Probolinggo, 2019)
To improve the students' mastery of the subject matter, the authors carry out the improvement of learning through Classroom Action Research (PTK). In relation to the above, the author would like to research with the title: Improved Understanding of Geometry and Measurement On Theme of Character Through Class III Demonstration Method SDN Sumberejo II Kecamatan Pakal Kota Surabaya . Based on the result of learning improvement on cycle I the lowest value is 40; average class 55,75; mastery learning 17% or 4 students from 24 students; and the material mastery level reaches 17%. This means that the results of the improvement of learning cycle I have not reached the criteria of success of planned improvements. In other words, in this cycle I, through repeated addition method of demonstration and repeated reduction in the learning of mathematics can not improve the understanding of multiplication concept and distribution in class III SDN Sumberejo II Kecamatan Pakal Kota Surabaya academic year 2017/2018.In cycle II the lowest value is 50; average grade 75,5; mastery learning 58% or 18 students from 24 student students: and the material mastery level reached 58%. This means that the result of the improvement of learning cycle II has not reached the planned success improvement criteria. In cycle II the lowest value is 60; average grade 80,5; mastery learning 92% or 22 students from 24 student students: and material mastery level reached 92%. This means that the result of the improvement of learning cycle II has reached even beyond the criteria of success of planned improvements. In other words, in cycle II through the method of repeated addition summation and repetitive reduction can improve the understanding of multiplication concepts and the division of mathematics learning in class III SDN Sumberejo II Kecamatan Pakal Kota Surabaya academic year 2017/2018